Noninvasive Detection of Macrophage-rich Atherosclerotic Plaque in Hyperlipidemic Rabbits using ‘Positive Contrast’ Magnetic Resonance Imaging - Korosoglou, Grigorios (2008)
OBJECTIVES: To identify macrophage-rich atherosclerotic plaque non-invasively by the combined use of systemic administration of superparamagnetic nanoparticles with magnetic resonance imaging (MRI), using a positive contrast off-resonance imaging sequence (Inversion Recovery with ON-resonant water suppression: IRON). BACKGROUND: The sudden rupture of macrophage-rich atherosclerotic plaques can trigger the formation of an occlusive thrombus in coronary vessels, resulting in acute myocardial infarction. Therefore, a noninvasive technique that can identify macrophage-rich plaques and thereby assist with risk stratification of patients with atherosclerosis would be of great potential clinical utility. METHODS: Experiments were conducted on a clinical 3T MRI scanner in seven heritable hyperlipidemic and four control rabbits. Monocrystalline iron-oxide nanoparticles (MION)-47 were administrated intravenously (two doses of 250μmol Fe/kg), and animals underwent serial IRON-MRI before injection of the nanoparticles and serially after 1, 3 and 6 days. RESULTS: After administration of MION-47, a striking signal enhancement was found in areas of plaque only in hyperlipidemic rabbits. The magnitude of enhancement on MR-images had a high correlation with the number of macrophages determined by histology (p<0.001) and allowed for the detection of macrophage-rich plaque with high accuracy (AUC=0.92, SE=0.04, 95% CI=0.84-0.96, p<0.001). No significant signal enhancement was measured in remote areas without plaque by histology and in controls without atherosclerosis. CONCLUSION: IRON-MRI in conjunction with superparamagnetic nanoparticles is a promising approach for the noninvasive evaluation of macrophage-rich, vulnerable plaques.